APEC’s Bold Higher Education Agenda: Will Anyone Notice? - Ziguras, Christopher (International Higher Education, 2014)
APEC is becoming increasingly interested in fostering greater cooperation and exchange in higher education across the Asia Pacific region. This article describes the genesis of that interest and points to some ongoing tensions that will continue to complicate regional initiatives.